Analisis Nilai Moral dalam Novel Anak Sejuta Bintang Karya Akmal Nasery Basral sebagai Alternatif Bahan Ajar SMA - Elok Setyo Pertiwi; Ika Septiana (Universitas PGRI Semarang, 2023)
This Study aims to Find and describe the moral values contained in the children’s novel a millon stars by akmal nasery basral. This research use desciptive qualitatif approach. The results of this study found in the ‘asb’ novel are the moral value of wisdom (bj), the moral value of compassion (ks), the moral value of not giving up (tpa), the moral value of discipline (d), the moral value of being generous (de), the moral value of being helpful (sm), pateint moral value (s), diligent moral value (j), hard work moral value (kk), responsibility moral value (c), courageous moral value (b), firm moral values (tgs), tough moral values (tgr), tenacious moral values (u), fair moral values (a), and orderly (t).Keywords: analysis of moral values, alternative teaching materials, in novels AbstrakPenelitian ini bertujuan untuk menemukan dan mendeskripsikan nilai-nilai moral yang terkandung di dalam Novel ‘Anak Sejuta Bintang’ karya Akmal Nasery Basral. Penelitian ini menggunakan pendekatan Deskriptif Kualitatif. Hasil dari penelitian ini ditemukan dalam novel ‘asb’ adalah nilai moral bijaksana (bj), nilai moral kasih sayang (ks), nilai moral tidak putus asa (tpa), nilai moral disiplin (d), nilai moral dermawan (de), nilai moral suka menolong (sm), nilai moral sabar (s), nilai moral tekun (tk), nilai moral jujur (j), nilai moral kerja keras (kk), nilai moral tanggung jawab (tj), nilai moral cerdas (c), nilai moral berani (b), nilai moral tegas (tgs), nilai moral tegar (tgr), nilai moral ulet (u), nilai moral adil (a), dan tertib (t).Kata kunci: analisis nilai moral, alternatif bahan ajar, dalam novel